IGM constraints from the SDSS-III/BOSS DR9 Lyα forest transmission probability distribution function - Lee, K.-G.; Hennawi, J.P.; Spergel, D.N.; Weinberg, D.H.; Hogg, D.W.; Viel, Matteo; Bolton, James S.; Bailey, S.; Pieri, M.M.; Carithers, W.; Schlegel, D.J.; Lundgren, B.; et al. (American Astronomical Society, 2015)
The Lyα forest transmission probability distribution function (PDF) is an established probe of the intergalactic medium (IGM) astrophysics, especially the temperature-density relationship of the IGM. We measure the transmission PDF from 3393 Baryon Oscillations Spectroscopic Survey (BOSS) quasars from Sloan Digital Sky Survey Data Release 9, and compare with mock spectra that include careful modeling of the noise, continuum, and astrophysical uncertainties. The BOSS transmission PDFs, measured at langzrang = [2.3, 2.6, 3.0], are compared with PDFs created from mock spectra drawn from a suite of hydrodynamical simulations that sample the IGM temperature-density relationship, γ, and temperature at mean density, T 0, where T(Δ) = T 0Δγ – 1. We find that a significant population of partial Lyman-limit systems (LLSs) with a column-density distribution slope of βpLLS ~ – 2 are required to explain the data at the low-transmission end of transmission PDF, while uncertainties in the mean Lyα forest transmission affect the high-transmission end. After modeling the LLSs and marginalizing over mean transmission uncertainties, we find that γ = 1.6 best describes the data over our entire redshift range, although constraints on T 0 are affected by systematic uncertainties. Within our model framework, isothermal or inverted temperature-density relationships (γ ≤ 1) are disfavored at a significance of over 4σ, although this could be somewhat weakened by cosmological and astrophysical uncertainties that we did not model.